1992
DOI: 10.1128/aac.36.7.1352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the combination of lipopolysaccharide-specific monoclonal antibodies and sparfloxacin against Pseudomonas aeruginosa pneumonia in neutropenic mice

Abstract: The effects of the combination of a murine monoclonal antibody (MAb) (20,26,29). Past studies have supported the possibility that MAb specific for the lipopolysaccharide (LPS) 0 side chain of P. aeruginosa, which has serotype-specific opsonic activity, is a possible candidate for the treatment of P. aeruginosa pneumonia (5,16,19,30). Although a previous investigator (18) indicated that neutropenia adversely affects the therapeutic efficacy of antibody in pseudomonal pneumonia, hyperimmune intravenous immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Administration of human and murine IgG antiflagella MAbs 1 h postchallenge also saved mice when as little as 1 to 2 ,ug per mouse was used (28,29). A similarly high dose of anti-LPS MAb was previously required for protection in the neutropenic pneumonia model (20), suggesting the relative stringency of the model as far as antibody-mediated protection is concerned.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Administration of human and murine IgG antiflagella MAbs 1 h postchallenge also saved mice when as little as 1 to 2 ,ug per mouse was used (28,29). A similarly high dose of anti-LPS MAb was previously required for protection in the neutropenic pneumonia model (20), suggesting the relative stringency of the model as far as antibody-mediated protection is concerned.…”
Section: Discussionmentioning
confidence: 99%
“…A neutropenic murine model ofP. aeruginosa pneumonia was used as described previously (20). Five-week-old specific-pathogenfree female Slc:ICR mice were obtained from Shizuoka Agricultural Cooperation Associations for Laboratory Animals, Shizuoka, Japan.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also demonstrated that human recombinant IL-8 at a range of 6.25 to 25 ng/ml enhanced the opsonophagocytic killing of P. aeruginosa It-1 strain by human neutrophils in a dose-dependent manner. The bactericidal action was complement-dependent, and mediated by a serotype-specific, anti-LPS MAb (13). This range of IL-8 was shown to be clinically achievable in sputum samples or BAL fluids from patients with pneumonia or CAD (14,16,17).…”
mentioning
confidence: 99%